2003
DOI: 10.1046/j.1432-1033.2003.03602.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on structure–function relationships of indolepyruvate decarboxylase from Enterobacter cloacae, a key enzyme of the indole acetic acid pathway

Abstract: Enterobacter cloacae, isolated from the rhizosphere of cucumbers, produces large amounts of indole‐3‐acetic acid. Indolepyruvate decarboxylase, the key enzyme in the biosynthetic pathway of indole‐3‐acetic acid, catalyses the formation of indole‐3‐acetaldehyde and carbon dioxide from indole‐3‐pyruvic acid. The enzyme requires the cofactors thiamine diphosphate and magnesium ions for catalytic activity. Recombinant indolepyruvate decarboxylase was purified from the host Escherichia coli strain JM109. Specificit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(85 citation statements)
references
References 49 publications
2
82
0
Order By: Relevance
“…The amino acid sequences of the ipd gene product and KdcA were aligned with the sequences of two well-characterized and homologous keto acid decarboxylating enzymes, yeast pyruvate decarboxylase (Pdc1p_SacCe) and indolepyruvate decarboxylase of Enterobacter cloacae (IpdC_EntCl) (11,31). KdcA, pyruvate decarboxylases, and indolepyruvate decarboxylases all depend on TPP and Mg 2ϩ as cofactors.…”
Section: Homology Of Kdca To Other Tpp-dependent Decarboxylasesmentioning
confidence: 99%
See 2 more Smart Citations
“…The amino acid sequences of the ipd gene product and KdcA were aligned with the sequences of two well-characterized and homologous keto acid decarboxylating enzymes, yeast pyruvate decarboxylase (Pdc1p_SacCe) and indolepyruvate decarboxylase of Enterobacter cloacae (IpdC_EntCl) (11,31). KdcA, pyruvate decarboxylases, and indolepyruvate decarboxylases all depend on TPP and Mg 2ϩ as cofactors.…”
Section: Homology Of Kdca To Other Tpp-dependent Decarboxylasesmentioning
confidence: 99%
“…Several regions were highly conserved, including the regions containing residues catalyzing the transition state intermediate during catalysis ( Fig. 2) (21) and residues involved in binding of the substrate and cofactors (31). The alignment in Fig.…”
Section: Homology Of Kdca To Other Tpp-dependent Decarboxylasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant amounts of trimeric or tetrameric oligomers were not observed by gel filtration, dynamic light scattering, or analytic ultracentrifugation at higher concentrations of enzyme, including the conditions of crystallization (17; A. K. Steinbach et al, submitted for publication). Most ThDP-dependent enzymes are arranged as homotetramers, such as POX from Lactobacillus plantarum (56), benzoylformate decarboxylase from Pseudomonas putida (23), indolepyruvate decarboxylase from Enterobacter cloacae (54), or pyruvate decarboxylase from Zymomonas mobilis (41). Bacterial AHAS reveals a common ␣ 2 ␤ 2 tetrameric structure (21, 51), whereas AHAS from Arabidopsis thaliana (9) and transketolase from Saccharomyces cerevisiae (59) represent examples of dimeric ThDP enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Besides decarboxylation of indolepyruvate, IPDCs can decarboxylate a number of α-keto acids, including pyruvate, benzoylformate and phenylpyruvate with different catalytic efficiencies (Fedorov et al 2010). The direct involvement of these enzymes in IAA biosynthesis was shown for Azospirillum brasilense, Enterobacter cloacae, Pantoea agglomerans (Schütz et al 2003a;Spaepen et al 2007) and Methylobacterium extorquens (Fedorov et al 2010). In a previous study we have detected PDC activity in P. serpens cell extracts and suggested that this enzyme, that participates in the alcoholic fermentation, would reoxidize a portion of the NADH produced in the very active glycolytic pathway of the flagellate.…”
Section: Introductionmentioning
confidence: 99%